EFEKTIVITAS PENGGUNAAN MODEL DISCOVERY LEARNING DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI KELAS X SMK NEGERI 1 LUMUT - Kurniawan Giawa; Nunik Ardiana; Agus Saleh (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
The aim of this study was to describe the effectiveness of using discovery learning model on students’ mathematical communication ability on the topic of trigonometric at the tenth grade students of SMK Negeri 1 Lumut. The research was conducted by applying experimental method (one group pretest posttest design) with 33 students as the sample and they were taken by using cluster random sampling technique from 455 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using discovery learning model was 3.89 (very good category) and (b) the average of students’ trigonometric achievement before using discovery learning model was 43.84 (fail category) and after using discovery learning model was 88.78 (very good category). Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 22) and N-Gain formulation, the result showed the significant value was less than 0.05 (0.000<0.05) and g= 0.81 (high category). It means, using discovery learning model gave high effect on students’ mathematical communication ability on the topic of trigonometric at the tenth grade students of SMK Negeri 1 Lumut